Factors associated with initiation of antiretroviral therapy in the advanced stages of HIV infection in six Ethiopian HIV clinics, 2012 to 2013 - Nash, Denis (J Int AIDS Soc, 2016)
INTRODUCTION: Most HIV-positive persons in sub-Saharan Africa initiate antiretroviral therapy (ART) with advanced infection (late ART initiation). Intervening on the drivers of late ART initiation is a critical step towards achieving the full potential of HIV treatment scale-up. This study aimed to identify modifiable factors associated with late ART initiation in Ethiopia. METHODS: From 2012 to 2013, Ethiopian adults (n=1180) were interviewed within two weeks of ART initiation. Interview data were merged with HIV care histories to assess correlates of late ART initiation (CD4+ count <150 cells/µL or World Health Organization Stage IV). RESULTS: The median CD4 count at enrolment in HIV care was 263 cells/µL (interquartile range (IQR): 140 to 390) and 212 cells/µL (IQR: 119 to 288) at ART initiation. Overall, 31.2% of participants initiated ART late, of whom 85.1% already had advanced HIV disease at enrolment. Factors associated with higher odds of late ART initiation included male sex (vs. non-pregnant females; adjusted odds ratio (aOR): 2.02; 95% CI: 1.50 to 2.73), high levels of psychological distress (vs. low/none, aOR: 1.96; 95% CI: 1.34 to 2.87), perceived communication barriers with providers (aOR: 2.42, 95% CI: 1.24 to 4.75), diagnosis via provider initiated testing (vs. voluntary counselling and testing, aOR: 1.47, 95% CI: 1.07 to 2.04), tuberculosis (TB) treatment prior to ART initiation (aOR: 2.16, 95% CI: 1.43 to 3.25) and a gap in care of six months or more prior to ART initiation (aOR: 2.02, 95% CI: 1.10 to 3.72). Testing because of partner illness/death (aOR: 0.64, 95% CI: 0.42 to 0.95) was associated with lower odds of late ART initiation. CONCLUSIONS: Programmatic initiatives promoting earlier diagnosis, engagement in pre-ART care, and integration of TB and HIV treatments may facilitate earlier ART initiation. Men and those experiencing psychological distress may also benefit from targeted support prior to ART initiation.